If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25(2x + -1) = 6(x + 3) + 3x Reorder the terms: 25(-1 + 2x) = 6(x + 3) + 3x (-1 * 25 + 2x * 25) = 6(x + 3) + 3x (-25 + 50x) = 6(x + 3) + 3x Reorder the terms: -25 + 50x = 6(3 + x) + 3x -25 + 50x = (3 * 6 + x * 6) + 3x -25 + 50x = (18 + 6x) + 3x Combine like terms: 6x + 3x = 9x -25 + 50x = 18 + 9x Solving -25 + 50x = 18 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -25 + 50x + -9x = 18 + 9x + -9x Combine like terms: 50x + -9x = 41x -25 + 41x = 18 + 9x + -9x Combine like terms: 9x + -9x = 0 -25 + 41x = 18 + 0 -25 + 41x = 18 Add '25' to each side of the equation. -25 + 25 + 41x = 18 + 25 Combine like terms: -25 + 25 = 0 0 + 41x = 18 + 25 41x = 18 + 25 Combine like terms: 18 + 25 = 43 41x = 43 Divide each side by '41'. x = 1.048780488 Simplifying x = 1.048780488
| v=4/3Π×9^ | | Z/1.6=1.1 | | 4x^3+2x^2+0.25x=0.173 | | x^2-y^2=201 | | 2=(x-1.97)/1.97 | | 2x-1/x^2=0 | | ln(4x^2)+ln(8)=5 | | 4/3•3.14•8 | | 8+7=12x-3-8x+1 | | 3x/7=10-x/2 | | y+7x=32 | | x^(3/4)=4 | | 2b+3(3b+19)=25 | | 2y-3x=-48 | | 3x+2y=-48 | | (4C-1)(5C+3)=0 | | xNy=2xy^2 | | 11x(751+209)= | | -2+5x=3x | | (-3b-1/4)-8 | | 8-2(7x-4)=6x-4 | | y=e^4lnx | | 204-(577-512)= | | 207-(577-512)= | | x^2+6x-36=-3 | | .33(9-6x)=x | | tan(x)=3.7 | | 12t^2-24t=0 | | 18*(480+859)= | | 7/x=3/4 | | X^2-12x-21=10 | | 12x-6x-7x=9 |